Enzymatic synthesis of structured lipids from sacha inchi (Plukenetia volubilis) oil with capric acid via acidolysis reaction in stirred tank and packed bed mini reactors (2024)
ABSTRACT: The present study describes an efficient and sustainable synthesis method for producing functional triglycerides (FTs) by conducting an acidolysis reaction of sacha inchi (Plukenetia volubilis) oil with capric acid (C10), catalyzed by Rhizopus oryzae (RO) lipase immobilized in low-cost corn cob powder, to obtain medium-large-medium chain (MLM) triglycerides. Initially, acidolysis reactions were performed between sacha inchi oil, C10, and the immobilized enzyme in a stirred tank at various temperatures (35 ◦C, 45 ◦C, 55 ◦C, and 59 ◦C), different molar ratios (1:2, 1:3, 1:4 oil:fatty acid), and various hydrolytic enzyme activities (83.6, 124, and 217 IU/mg). Subsequently, to optimize the degree of incorporation, the best condition from the stirred tank reactions (45 ◦C, 1:3 M ratio, and 217 U of hydrolytic activity) was selected, considering the highest nutritional quality of the lipid in terms of the migration of the sn2 position, and was tested in a packed bed reactor with a spatial time of 112 min, residence time of 107 min, and a flow rate of 0.5 mL/min. The highest incorporation degree achieved in packed bed reactor was 36% at 45 ◦C. Afterward, it was developed for the best condition an integrative platform for the recycling of the RO lipase immobilized in low-cost corn cob powder (up to four successive cycles without any make up). Subsequent assays on the functional triglycerides revealed atherogenic and thrombogenicity lipid index values of 0.04 ± 0.10 and 4.15 ± 0.05, respectively, which were lower than those of pure sacha inchi oil, indicating the potential to enhance the nutritional quality of the oil through C10 incorporation.